AAβ public key cryptosystem - a comparative analysis against RSA and ECC - Kamel Ariffin, Muhammad Rezal; Mahad, Zahari (IEEE, 2012)
This paper aims to provide a comparative analysis between probabilistic and deterministic security models. We provide a benchmark by practically implementing and comparing three ciphers - AAβ, RSA and ECC. This paper provides the algorithms to implement these ciphers as well as highlights the operating time and performance for varying key sizes of 128/1024/3072, 160/2048/6144 and 192/4096/12288 bits. We target our implementation to justify if the probabilistic model - AAβ, can perform equivalently against deterministic models so as to be considered to be used in practical scenarios today.